Efficacy of baricitinib in severe coronavirus disease 2019 - Ahmed M A E F Amer; Doaa B Mousa; Azza A Ahmed (Egyptian Journal of Chest Disease and Tuberculosis, 2023)
Background Coronavirus disease 2019 (COVID-19) binds to angiotensin-converting enzyme through a viral spike protein prompting an inflammatory cascade. Baricitinib, an oral drug, is a selective inhibitor of Janus kinase (JAK) 1 and 2 and interferes with the intracellular signaling pathway of many cytokines and in combination with remdesivir may give good results in severe COVID-19 infection. Aim The aim was to assess the effect of baricitinib in severe COVID-19 pneumonia. Patients and methods A total of 30 patients with SARS-CoV-2-confirmed positive cases by nasopharyngeal swab/reverse transcriptase PCR with severe pneumonia received oral baricitinib 4 mg daily, and patients were followed for at least 14 days, unless previously discharged or dead. Results Patients were admitted to the ICU, with a mean duration of 11 days. All patients received high-flow oxygen with nonrebreathing mask. A total of 18 (60%) patients improved and 12 (40%) patients died. Moreover, 15 patients had comorbidities, and mortality was high in this group (10 patients). No serious adverse effects of baricitinib were detected in our study. All patients were hypoxic at admission. The mean oxygen saturation on room air was 70%. There was a statistically significant improvement in oxygenation on discharge after receiving treatment, with mean oxygen saturation of 90% on room air. Conclusion Baricitinib with remdesivir improves clinical status and oxygen saturation in patients with severe COVID-19 pneumonia with no serious adverse effects.